CFD Simulations to Calculate the Resistance of A 17.500-DWT Tanker - Dian Purnamasari; I Ketut Aria Pria Utama; I Ketut Suastika (IPTEK Journal of Proceedings Series, 2018)
Numerical simulations have been carried out to determine free surface flow around a tanker 17.500 hull form for which experimental results are available. The SST turbulence model was used in Ansys CFX. The numerical methodology is found to be appropriate for simulating the turbulent flow around a model in order to estimate model total resistance. The computational results are presented in a non-dimensional form. By the numerical results, total resistance is calculated for the ship model and the result is satisfactory with regard to the experimental results were compared